2013
DOI: 10.1590/s1516-35982013000100001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the spermatozoa: oocyte ratio, water volume and water temperature on artificial fertilization and sperm activation of cascudo-preto

Abstract: -The objective of this study was to evaluate the effects of water volume and water temperature on the sperm motility duration and the number of spermatozoa, and the water volume on the fertilization rates of oocytes of Rhinelepis aspera. Experiments were carried out to evaluate the effect of semen dilutions (1.74×10-5 , 1.74×10 -4 , 1.74×10 -3 , 1.74×10 -2 , 1.74×10 -1 and 1.00 mL of sperm.mL -1 of water) and water temperature (5, 10, 15, 20, 25, 30, 35, 40, 45, and 50 °C) on spermatozoa motility duration. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…A handful of studies have indicated that spermatozoon motility is prolonged at low temperatures (Lahnsteiner & Mansour ; Bombardelli et al . ), and this is generally accepted (Fig. ).…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…A handful of studies have indicated that spermatozoon motility is prolonged at low temperatures (Lahnsteiner & Mansour ; Bombardelli et al . ), and this is generally accepted (Fig. ).…”
Section: Introductionmentioning
confidence: 76%
“…This reduction in duration of motility may be due to limited energy resources and to the influence of temperature on metabolic processes. In addition, temperature of the activation solution appears to be the most important physicochemical condition affecting spermatozoon motility (Bombardelli, Sanches, Baggio, Sykora, Souza, Tessaro & Pianal ); hence, a better understanding of the influence of water temperature is crucial to improvement of artificial reproduction methods (Alavi, Rodina, Policar, Kozak, Psenicka & Linhart ; Rodina, Gela, Kocour, Alavi, Hulak & Linhart ).…”
Section: Introductionmentioning
confidence: 99%
“…It may also be used as a way of assessing the quality of the broodstocks. Furthermore, such assessment is fundamental in artificial fertilization procedures, since the amount of spermatozoa necessary for fertilization is variable among the South American fish species (Bombardelli et al, 2006(Bombardelli et al, , 2013Shimoda et al, 2007;Sanches et al, 2009;Fig. 5.…”
Section: Discussionmentioning
confidence: 99%
“…Temperature of the activation medium has been shown to affect motility duration, speed and fertilising ability of fish spermatozoa (Billard et al ., ; Bombardelli et al ., ; Cosson et al ., ; Dadras et al ., ). Lahnsteiner et al .…”
Section: Introductionmentioning
confidence: 97%
“…Temperature of the activation medium has been shown to affect motility duration, speed and fertilising ability of fish spermatozoa Bombardelli et al, 2013;Cosson et al, 1985;Dadras et al, 2016). Lahnsteiner et al (1997) reported that L. lota sperm remained immotile in a saline solution with osmolality of 400 mOsm kg −1 and pH below 7.4 led to a marked decrease in motility.…”
Section: Introductionmentioning
confidence: 99%